2004
DOI: 10.1542/peds.2003-0635-l
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Programs to Teach Firearm Injury Prevention Skills to 6- and 7-Year-Old Children

Abstract: ABSTRACT. Background. Each year, hundreds of children unintentionally kill or injure other children while playing with firearms in the United States. Although the numbers of these deaths and injuries are distressing, few prevention programs have been developed to prevent gun play among children.Objective. This study compared the efficacy of 2 programs designed to prevent gun play among young children.Design. A posttest-only, control group design with 2 treatment groups was used. Children were randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(55 citation statements)
references
References 18 publications
5
50
0
Order By: Relevance
“…The results of , , Gatheridge et al (2004), and Kelso et al (2007) demonstrated the importance of in situ training for teaching safety skills to children. Although BST was effective for some children, in situ training resulted in successful performance for all children who did not perform the safety skills following BST.…”
Section: Behavioral Skills Training (Bst)mentioning
confidence: 90%
See 3 more Smart Citations
“…The results of , , Gatheridge et al (2004), and Kelso et al (2007) demonstrated the importance of in situ training for teaching safety skills to children. Although BST was effective for some children, in situ training resulted in successful performance for all children who did not perform the safety skills following BST.…”
Section: Behavioral Skills Training (Bst)mentioning
confidence: 90%
“…To conduct a skills assessment, the trainer tells the child that he or she will act out a situation and ask the child to "show me what you would do in this situation" (e.g., Gatheridge et al, 2004;Miltenberger & Olson, 1996). The trainer then creates the scenario and assesses the child's skills as the child responds to the simulated safety threat.…”
Section: Skills Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Two important risk factors associated with unintentional firearm injuries in children are unsafe firearm storage and children's tendency to play with guns they find. Recently, researchers have evaluated procedures to prevent gun play (e.g., Gatheridge et al, 2004;. and Miltenberger et al (2004) showed that behavioral skills training (BST) was effective for some children, but that the effectiveness of BST was enhanced with the addition of in situ training for others.…”
Section: ____________________________________________________________mentioning
confidence: 99%